ANALISIS HUKUM PENGGUNAAN SURAT KUASA YANG MELEBIHI TUJUANNYA (Studi Putusan Mahkamah Agung Republik Indonesia Nomor 1189K/Pdt/2017 dan Putusan Pengadilan Negeri Cibinong Nomor 104//Pdt.G/2012/Pn. Cbn.) - Raskita J.F. Surbakti (Magister Hukum Universitas HKBP Nommensen, 2022)
Misuse of power of attorney in a civil case includes, among other things, if the power of attorney contains beyond the limit of authority granted by the power of attorney to the recipient of the power of attorney, so that the power of attorney can be used to commit a legal act that is inconsistent with or deviates from the intention or purpose of the person giving the power of attorney. power. The power of attorney is often a problem in view of the restrictions, legal consequences and protections that connect with third parties. The problem of power in this thesis is reviewed based on the decision No. 104 / PDT.G / 2012 / PN.Cbn and Decision Number 1189K / Pdt / 2017. The formulation of the research problem is: discussing the regulation of limiting the provision of power of attorney based on civil law in Indonesia, due to the legal agreement of the beneficiary that exceeds his authority and legal protection of third parties who suffer losses due to the use of a power of attorney beyond their authority The type of research used in this thesis is normative legal research, the nature of the research used is descriptive analytical research. This study uses library data collection techniques (library research). The data analysis used in this thesis research is qualitative data analysis. The limitations on granting power of attorney in the Civil Code are seen in Article 1794 to Article 1798 of the Civil Code which explains the granting of power based on what the giver is responsible for with the substance of the power of attorney's wages, form of power, power of attorney, provisions for exercising power of attorney and whoever can receive power. Decision Number 1189K / Pdt / 2017, the power of attorney even in the form of apparent power of attorney made based on the receivables of the power of attorney is not allowed by the court to make a sale and purchase deed based on a power of attorney against him even though the power of attorney has a debt against him Decision No. 104 / PDT.G / 2012 / PN.Cbn explained that in relation to the legal position based on the results of the court punishing the power of attorney to return what is the right of the power of attorney is a form of proof of the power to bind the power of attorney as a form of agreement. The agreement that has been agreed upon is only to offer and find a buyer but is carried out in fact selling the object of the dispute. Third party protection is obtained based on Article 1491 of the Civil Code which reads: